Fundamentals of space business and economics - Gurtuna, Ozgur (SpringerBriefs in Space Development, 2013)
This book provides an overview of key topics related to space business and management. Case studies and an integrative section are included to illustrate the fundamental concepts and to build intuition. Key topics in the field, such as risk management and cost management, are covered in detail.